PENGARUH KREATIVITAS MAHASISWA DAN KOMUNIKASI INTERPERSONAL DENGAN DOSEN TERHADAP PRESTASI BELAJAR MAHASISWA PRODI PENDIDIKAN EKONOMI STKIP PGRI SUMATERA BARAT - Virgo, Ujang - (Pendidikan Ekonomi, 2014)
This research was conducted in the study program of economic education STKIP PGRI West Sumatra, on the effect of student creativity and interpersonal communication with faculty on student achievement education department of economics. The purpose of this study were (1) To determine the effect of creativity of students on student achievement education department of economics STKIP PGRI West Sumatra. (2) To determine the effect of interpersonal communication with faculty on student learning achievement of the education department of economics STKIP PGRI West Sumatra. (3) To determine the effect of students creativity and interpersonal communication with faculty on student learning achievement of the education department of economics STKIP PGRI West Sumatra.The results of data analysis showed that (1) There is a positive and significant impact of student creativity on student achievement education department of economics STKIP PGRI West Sumatra, this is evidenced by the regression coefficient of 0.560, with a value of 4,927 t count> t table 1.6622 seen from sig 0.000 <Î± = 0.05 with a sig of 0.000, which is smaller than Î± = 0.05. (2) There is a positive and significant impact anatara interpersonal communication with faculty on student achievement education department of economics STKIP PGRI West Sumatra, this is evidenced by the regression coefficient of 0.528, with a value of 3,352 t count> t table 0.000 1.6622 seen from the sig <. Î± = 0.05 (3) There is a significant effect between students creativity and interpersonal communication with faculty on student achievement education department of economics STKIP PGRI West Sumatra, this is evidenced by the regression coefficient of F 105.146 sebeser> F table value of 3.10 and a significant of 0.002. Sig value <Î±, namely (0.000 <0.05).